Clinical and Epidemiological Assessment of Children and Adolescents Hospitalized with SARS-CoV-2 in the Pre-Amazon Region - Marilene Ribeiro; Luis Sousa; Johnatha Oliveira; Derek Pinto; Luís Batista; Luis Lobato; Lucas Sousa; Hivylla Ferreira; Valdenice Santos; Valéria Fontes; Diana Bastos; Flor de Maria Silva; et al. (Biomedicines, 2024)
Introduction: SARS-CoV-2 infection usually presents similarly to other respiratory viral pathogens. Children and adolescents do not present as a group that is highly affected by the disease, having low infection rates. However, limited publications are associated with the findings of pneumonia in pediatric patients with COVID-19. Objective: To analyze the clinical and epidemiological aspects of children and adolescents hospitalized with SARS-CoV-2 in a pre-Amazon region. Methods: A retrospective study, carried out in four public hospitals in São Luís, Brazil where medical records of children and adolescents aged from 0 to 13 years, of both sexes, with clinical diagnosis of community-acquired pneumonia were evaluated from March 2020 to March 2021. Results: Almost 40.0% of children were aged between 1 year and 5 years. Of the 128 children who had SARS-CoV-2, 3 are of indigenous ethnicity. Additionally, 78.6% of the children had fever and there was no significant difference between COVID-19 patients and those of other respiratory viruses. Eighteen patients had chronic neurological disease, which is the most common comorbidity observed in patients with coronavirus infection. Ground glass opacity attenuation was observed in 24.8% of children and adolescents with COVID-19. Anemia and increased inflammatory response markers were related to SARS-CoV-2 infection. More than 90.0% of patients admitted to hospital, regardless of etiology, were treated with antibiotics. Eighteen patients died. Pediatric multisystem inflammatory syndrome (PMIS) was diagnosed in 17 patients. Conclusions: SARS-CoV-2 in children and adolescents is mild, but the condition of patients with PMIS is more serious, with an increase in inflammatory biomarkers which can lead to death. Therefore, rapid diagnosis and differentiation of agents causing respiratory diseases are necessary for better therapeutic decision making, since the results of this study make us question the excessive use of antibiotics without meeting well-defined clinical–epidemiological criteria.